The Significance of Cultural Factors in International Business in Eastern Asia - Skulska, Bogusława; Skulski, Przemysław (Znaczenie czynników kulturowych w biznesie międzynarodowym w Azji Wschodniej, 2010)
Doing business in East Asia is challenging. The scope of its market is enormous and cultural differences among its business people extreme. But when handled correctly, doing business in Asia is a wonderful adventure. The overview of the most important religious systems, elements of culture and main cultural orientations in East Asia region allowed to indicate the most significant specific features which to a large extent affect doing international business.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 136, s. 184-200
Keywords: international business; East Asia; cultural factors